2003
DOI: 10.1159/000072015
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pulmonary Nodules in a Patient with Crohn’s Disease

Abstract: Crohn’s disease (CD) can be associated with respiratory involvement. Multiple pulmonary nodules are an infrequent finding in patients with CD. When they are found, histology usually shows sterile necrobiotic nodules, which are spherical aggregates of neutrophils, which frequently cavitate. We report a patient with inactive CD treated with mesalazine, who presented with multiple pulmonary nodules. Transthoracic biopsy of one of the nodules disclosed a benign, nongranulomatous inflammatory lymphoid infiltration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Noncaseating epithelioid granulomas are reported and have an association with IBD, particularly CD [4]. Golpe et al reported nongranulomatous lymphoid infiltration as the histopathology of the pulmonary nodule in their case report [6]. On review of the published histology images from Golpe et al by our pathologist who specializes in gastrointestinal and pulmonary pathology, the images were interpreted as interstitial infiltration with a mixture of cells.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Noncaseating epithelioid granulomas are reported and have an association with IBD, particularly CD [4]. Golpe et al reported nongranulomatous lymphoid infiltration as the histopathology of the pulmonary nodule in their case report [6]. On review of the published histology images from Golpe et al by our pathologist who specializes in gastrointestinal and pulmonary pathology, the images were interpreted as interstitial infiltration with a mixture of cells.…”
Section: Discussionmentioning
confidence: 96%
“…Pulmonary nodules, however, are an uncommon manifestation of IBD with very few documented cases in the English-language literature, as cited in Table 1. Camus et al was one of the earliest authors to propose a link between pulmonary nodules and IBD and other case reports thereafter further solidify the finding of pulmonary nodules as an EIM of IBD [2][3][4][5][6][7][8]. In general, patients with pulmonary nodules related to IBD present with respiratory and constitutional symptoms, but inactive bowel disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 Nodular pulmonary amyloidosis associated with Crohn's disease and focal non-granulomatous lymphoid infiltration are other rare causes of lung nodules in Crohn's disease that can mimic necrobiotic lung nodules. 11,12 The small number of reported cases of necrobiotic nodules complicating Crohn's disease do not allow strong conclusions regarding therapy. Of the 4 reported patients, 3 responded to oral prednisone with radiological resolution, and one patient who was maintained on mesalamine at the time of diagnosis had complete radiological resolution with no additional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with corticosteroids or with appropriate medication such as sulfasalazine or mesalamine for the basic gastrointestinal disease appeared to be satisfactory for both diseases. Pneumonitis, in contrast, due either to sulphasalazine or mesalamine is a well-recognized adverse drug reaction in these patients (19).…”
mentioning
confidence: 99%